Mechanical Properties and Numerical Analyses of Basalt Fiber Crumb Rubber Mortars in Soft Rock Roadways - Jun-Ling Qin; Wei-Guo Qiao; Deng-Ge Lin; Shuai Zhang; Ji-Yao Wang (Advances in Civil Engineering)
The strength of crumb rubber mortars can be improved by the addition of basalt fibers. However, limited studies have been conducted on basalt fiber crumb rubber mortars (BF-CRM), and the constitutive model is still very immature. In this paper, uniaxial compressive stress-strain curves are obtained for several groups of BF-CRM specimens with different contents. By comparison with the GZH model, modified GZH parameters that can be used in a BF-CRM constitutive model are obtained. Then, taking the support scheme of the main substation of a mine as the background, FLAC3D is used to simulate the roadway support, BF-CRM replaces the ordinary mortars in the original support, and triaxial compression tests are performed at different confining pressures. In this way, the application of BF-CRM in roadway support is studied and analyzed.